EFEKTIFITAS BRAND EQUITY DALAM PURCHASE INTENTION TIKET MASKAPAI LOW COST CARRIER DI BANDARA SULTAN ISKANDAR MUDA ACEH BESAR - Ramadani Prawito; Dr. Mahyuzar, Drs, M.Si - (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2019)
ABSTRAK - Skripsi ini berjudul “Efektifitas Brand Equity Dalam Purchase Intention Tiket Maskapai Low Cost Carrier Di Bandara Sultan Iskandar Muda Aceh Besar”. Rumusan masalah dalam penelitian ini adalah Bagaimana efektifitas brand equity dalam purchase intention tiket maskapai low cost carrier di Bandara Sultan Iskandar Muda. Tujuan dari penelitian ini untuk ingin mengetahui efektifitas brand equity dalam purchase intention tiket maskapai low cost carrier di Bandara Sultan Iskandar Muda. Penelitian ini menggunakan teori The Expectancy Disconfirmation Theory yang dikemukakan oleh Richard L. Oliver pada tahun 1977 dan 1980. Objek dalam penelitian ini adalah purchase intention para penumpang yang  menggunakan maskapai low cost carrier (LCC). Sedangkan subjek dalam penelitian ini ialah para calon penumpang maskapai Citylink dan Lion Air yang berada di Bandara Sultan Iskandar Muda. Teknik pengumpulan data dari penelitian ini menggunakan wawancara, observasi. Hasil penelitian menunjukkan bahwa 8 dari 9 dari informan penelitian ini menunjukan sikap diskonfirmasi postif sedangkan 1 dari 8 informan melakukan diskonfermasi negative, informan lain memberikan diskonfirmasi sederhana dan diskonfirmasi positif. Ketujuh informan setuju untuk tetap menggunakan maskapai LCC untuk penerbangan selanjutnya, harga yang terjangkau menjadi faktor utama mereka untuk melakukan pembelian ulang maskapai LCC, Brand equity perusahaan akan mempengaruhi purchase intention atau pembelian ulang oleh konsumen maskapai LCC . Dalam penelitian ini, informan yang telah peneliti wawancarai cenderung memilih maskapai LCC untuk melakukan penerbangan dengan alasan harga tiket sesuai dengan budget yang mereka miliki. Artinya, konsumen maupun pelanggan memiliki minat transaksional terhadap maskapai LCC, dan secara tidak langsung telah memberi diskonfirmasi positif untuk kedua brand ini.Kata kunci: brand equity, purchase intention, the expectasi disconfermation theory The Effectiveness of Equity Brand  in Purchase Intention of Low Cost Carrier flight ticket in Sultan Iskandar Muda Airport in Aceh BesarABSTRACT - This Skripsi entitles “The Effectiveness of Equity Brand  in Purchase Intention of Low Cost Carrier flight ticket in Sultan Iskandar Muda Airport in Aceh Besar”. The problem formulation in this research is how the effectiveness of equity brand  in purchase intention of low cost carrier flight ticket in Sultan Iskandar Muda Airport. The purpose of this research is to seek the effectiveness of equity brand in purchase intention of low cost carrier flight ticket in Sultan Iskandar Muda Airport. This research used The Expectancy Disconfimartion Theory proposed by Richard L. Oliver in 1977 and 1980. The object of this research was the purchase intention of passengers who used the low cost carrier (LCC) of airline of Citilink and Lion Air. While the subjects in this research were passenger candidates of Citilink and Lion Air airline who were in Sultan Iskandar Muda Airport. The techniques of data collection used in this research were interview and observation. The result of this research showed that 8 out of 9 of informants in this research showed positive disconfirmation attitudes while 1 out of 8 informants made negative disconfirmation, and other informants gave simple disconfirmation and positive disconfirmation for the two airlines. The seven informants agreed to continue using LCC airline for the next flight. Affordable price was their main factor to repurchase the LCC airline. The company’s Equity Brand will affect the puchase intention or repeat purchase by LCC airline customers. In this research, those of informants who have been interviewed by the researcher tended to choose the LCC airline to make a flight with the reason that ticket price was suitable with their budget. It means that both customers and customers have a transactional interest in LCC airline and they had indirectly given positive disconfimation for these two brands. Keywords : equity brand, purchase intention, the expectation of disconfirmation theoryABSTRACT - This Skripsi entitles “The Effectiveness of Equity Brand  in Purchase Intention of Low Cost Carrier flight ticket in Sultan Iskandar Muda Airport in Aceh Besar”. The problem formulation in this research is how the effectiveness of equity brand  in purchase intention of low cost carrier flight ticket in Sultan Iskandar Muda Airport. The purpose of this research is to seek the effectiveness of equity brand in purchase intention of low cost carrier flight ticket in Sultan Iskandar Muda Airport. This research used The Expectancy Disconfimartion Theory proposed by Richard L. Oliver in 1977 and 1980. The object of this research was the purchase intention of passengers who used the low cost carrier (LCC) of airline of Citilink and Lion Air. While the subjects in this research were passenger candidates of Citilink and Lion Air airline who were in Sultan Iskandar Muda Airport. The techniques of data collection used in this research were interview and observation. The result of this research showed that 8 out of 9 of informants in this research showed positive disconfirmation attitudes while 1 out of 8 informants made negative disconfirmation, and other informants gave simple disconfirmation and positive disconfirmation for the two airlines. The seven informants agreed to continue using LCC airline for the next flight. Affordable price was their main factor to repurchase the LCC airline. The company’s Equity Brand will affect the puchase intention or repeat purchase by LCC airline customers. In this research, those of informants who have been interviewed by the researcher tended to choose the LCC airline to make a flight with the reason that ticket price was suitable with their budget. It means that both customers and customers have a transactional interest in LCC airline and they had indirectly given positive disconfimation for these two brands.Keywords : equity brand, purchase intention, the expectation of disconfirmation theory